2018
DOI: 10.1073/pnas.1803866115
|View full text |Cite
|
Sign up to set email alerts
|

1.1-billion-year-old porphyrins establish a marine ecosystem dominated by bacterial primary producers

Abstract: The average cell size of marine phytoplankton is critical for the flow of energy and nutrients from the base of the food web to higher trophic levels. Thus, the evolutionary succession of primary producers through Earth's history is important for our understanding of the radiation of modern protists ∼800 million years ago and the emergence of eumetazoan animals ∼200 million years later. Currently, it is difficult to establish connections between primary production and the proliferation of large and complex org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 71 publications
2
85
0
Order By: Relevance
“…The genuine absence or low concentration of TMAI in the Velkerri Formation is important because it distinguishes its environment from other Proterozoic formations such as the Barney Creek Formation (Brocks et al., ) and the 1.1 Ga El Mreïti Group (Gueneli et al., ). We therefore investigate whether the extremely low concentrations of TMAI reflect primary absence or are due to thermal breakdown or oxygen exposure during degradation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The genuine absence or low concentration of TMAI in the Velkerri Formation is important because it distinguishes its environment from other Proterozoic formations such as the Barney Creek Formation (Brocks et al., ) and the 1.1 Ga El Mreïti Group (Gueneli et al., ). We therefore investigate whether the extremely low concentrations of TMAI reflect primary absence or are due to thermal breakdown or oxygen exposure during degradation.…”
Section: Resultsmentioning
confidence: 99%
“…These geochemical conditions and biomarker assemblages are broadly comparable to black, finely laminated shales from the ca . 1.1 Ga El Mreïti Group in the Taoudeni Basin, Mauritania (Blumenberg et al., ; Gueneli et al., ). There, the presence of 2,3,4‐ and 2,3,6‐TMAI, in addition to iron speciation, and sulphur isotopes of pyrite and redox‐sensitive trace elements all suggest nearshore PZE conditions (Blumenberg et al., ; Gilleaudeau & Kah, ; Gueneli et al., ; Kah, Bartley, & Teal, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Silverman, Kopf, Bebout, Gordon, and Som (2019) showed that the nitrogen isotopic fractionation during N 2 fixation changes as a function of pN 2 in some species of cyanobacteria. As microbial N 2 fixation is thought to have arisen early in Earth's history (Stüeken, Buick, Guy, & Koehler, 2015;Weiss et al, 2016) and cyanobacteria may have dominated primary productivity through much of the Precambrian (Brocks et al, 2017;Gueneli et al, 2018), they could perhaps provide a long-term record of both pN 2 and the δ 15 N of atmospheric N 2 . However, because δ 15 N values of bulk marine sediments can be altered by a few permil during diagenesis (Robinson et al, 2012) and represent a mixture of biomass from N 2 -fixing and non-N 2 -fixing organisms, this would require the nitrogen isotopic analysis of discrete cyanobacterial fossils instead of bulk marine sediments.…”
Section: Introductionmentioning
confidence: 99%